2018
DOI: 10.1093/nar/gky562
|View full text |Cite|
|
Sign up to set email alerts
|

RBPJ binds to consensus and methylated cis elements within phased nucleosomes and controls gene expression in human aortic smooth muscle cells in cooperation with SRF

Abstract: Given our previous demonstration that RBPJ binds a methylated repressor element and regulates smooth muscle cell (SMC)-specific gene expression, we used genome-wide approaches to identify RBPJ binding regions in human aortic SMC and to assess RBPJ’s effects on chromatin structure and gene expression. RBPJ bound to consensus cis elements, but also to TCmGGGA sequences within Alu repeats that were less transcriptionally active as assessed by DNAse hypersensitivity, H3K9 acetylation, and Notch3 and RNA Pol II bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…It is widely accepted that transcription is regulated by the interplay of the multiprotein complexes [ 61 , 62 , 63 , 64 , 65 ]. Moreover, due to the presence of dominant activators or repressors co-occupying DNA regulatory sites, functions of a particular transcription factor might be limited to a subset of its binding sites [ 61 , 64 , 66 , 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely accepted that transcription is regulated by the interplay of the multiprotein complexes [ 61 , 62 , 63 , 64 , 65 ]. Moreover, due to the presence of dominant activators or repressors co-occupying DNA regulatory sites, functions of a particular transcription factor might be limited to a subset of its binding sites [ 61 , 64 , 66 , 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is widely accepted that transcription is regulated by the interplay of the multiprotein complexes [ 61 , 62 , 63 , 64 , 65 ]. Moreover, due to the presence of dominant activators or repressors co-occupying DNA regulatory sites, functions of a particular transcription factor might be limited to a subset of its binding sites [ 61 , 64 , 66 , 67 , 68 ]. For the p53 transcription factors family, interactions with distinct proteins may skew the binding of p53, p63 and p73 isoforms towards different sites in the genome and determine their specific activities [ 14 , 21 , 43 , 63 , 69 , 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, our computational analysis showed that DMRs from the T + WSD group were enriched in TF binding motifs, supporting the regulatory role of DNA methylation in modulating TF binding affinities 78 . As an example, RBPJ has been shown to control the expression of notch signaling genes 79 and to bind chromatin in a methylation-dependent fashion 80,81 .…”
Section: Discussionmentioning
confidence: 99%
“…This binding interaction not only displaces transcriptional repressors that are bound to RBPJ in the absence of active Notch but also facilitates the recruitment of transcription activators such as mastermind-like transcriptional coactivator (MAML) and histone acetyl transferases. We and others have shown that RBPJ binds to a number of SMC-specific promoters (8,38,39,44), and in vivo evidence suggests that Notch/RBPJ signaling is required for SMC differentiation from multiple precursors (5,8,15,21). We also identified a consensus motif (CATTCC) for the TEAD factors that have been implicated in muscle-selective gene expression and are transcriptional mediators of the Hippo signaling pathway [see Fu et al (12) for review].…”
Section: Int1dhs Activity Was Mediated By a 100-bp Conserved Regionmentioning
confidence: 70%